Dynamics of bank capital ratios and risk-taking: Evidence from US commercial banks - Faisal Abbas; Shoaib Ali (Cogent Economics & Finance, 2020)
This study aims to explore how different capital ratios influence the risk-taking of large commercial banks of the USA. The study collects the data from FDIC for commercial banks from 2003 to 2019. We use a two-step GMM method to manage the endogeneity, simultaneity, heteroscedasticity, and auto-correlations issue. The findings conclude that an increase in the risk-based capital ratios decreases the banks' risks. Empirical findings demonstrated a significant and positive association between non-risk-based capital ratios and bank risk-taking. The findings also demonstrate that an increase in capital buffer ratios decreases the banks' risks. The impact of capital ratios on risk-taking is heterogeneous for well and under-capitalized banks. The findings suggest that State-chartered member and non-member banks are inclined to take a higher risk than nationally chartered banks. The findings have implications for regulators to consider the State-chartered member, non-member, and nationally chartered banks while formulating the new guidelines for required capital ratios.
Keywords: G21; G28; G32; 330; capital buffer ratios; risk-based capital ratios; risk-taking; USA